2016
DOI: 10.3311/ppee.10018
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Probabilistic Technique for Optimal Allocation of Photovoltaic Based Distributed Generators to Decrease System Losses

Abstract: This paper presents a novel algorithm for modeling photovoltaic based distributed generators for the purpose of optimal planning of unbalanced distribution networks. The proposed algorithm utilizes sequential Monte Carlo method in order to accurately consider the stochastic nature of photovoltaic based distributed generators. An efficient algorithm based on Firefly optimization method is proposed for optimal placement of photovoltaic based distributed generators in unbalanced distribution network. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Many stochastic optimization approaches do exist in literature [51]. Among these methods, the Monte Carlo (sample average) approach has been identified as the most robust mechanisms to handle such as complex system with high level of uncertainties [49]. In the next section of this study, we use a stochastic optimization method called the sample average approximation to tackle the uncertainty.…”
Section: Methods Of Handling the Randomness In The Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Many stochastic optimization approaches do exist in literature [51]. Among these methods, the Monte Carlo (sample average) approach has been identified as the most robust mechanisms to handle such as complex system with high level of uncertainties [49]. In the next section of this study, we use a stochastic optimization method called the sample average approximation to tackle the uncertainty.…”
Section: Methods Of Handling the Randomness In The Designmentioning
confidence: 99%
“…e study finally concluded that dealing with uncertainties in the design though comes with a high computational cost is much more reliable. Reference [49] looked at a new probabilistic approach to optimally allocate PV distributed generators for the reduction of system losses. ey applied a Monte Carlo approach to model the uncertainties in the RES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation